Light Driven Active Transition of Switching Modes in Homogeneous Oxides/Graphene Heterostructure. Issue 11 (12th April 2019) - Chen, Xiaoli; Zeng, Kelin; Zhu, Xin; Ding, Guanglong; Zou, Ting; Zhang, Chen; Zhou, Kui; Zhou, Ye; Han, Su‐Ting
Abstract: Depending on the mobile species involved in the resistive switching process, redox random access memories and conductive bridge random access memories are widely studied with distinct switching mechanisms. Although the two resistance switching types have faithfully proved to be electrochemically linked in metal oxide‐based memristive devices, the corresponding photo‐induced transition has not yet been realized. Here, a photo‐induced transition through the integration of a graphene layer into a titanium oxide‐based memory device is demonstrated. Coupled with Raman mapping and an electron energy loss spectroscopy technique, the photo‐induced interaction at the heterostructure of graphene/titanium oxide are considered to dominate the transition process. Moreover, a negative differential resistance effect is observed by controlling the applied voltage, which can be credited to the saturation of trap centers (oxygen vacancies) and the increase of interfacial barrier at the graphene/titanium oxide heterojunction. Abstract : A photo‐induced transition from oxygen vacancy filament to metal filament is observed at the heterostructure of titanium oxides/graphene. The photo‐induced interaction at the heterostructure is demonstrated to account for the transition. Moreover, voltage controlled negative differential resistance effect is obtained. The results can provide significant insight into designing and manipulating memristive devices based on heterostructured materials.